PENGARUH INSEKTISIDA PROFENOFOS TERHADAP FEKUNDITAS DAN DAYA TETAS TELUR CACING TANAH (Lumbricus rubellus) - Marlinda, Tuti; Nurhadi, Nurhadi; Widiana, Rina (Pendidikan Biologi, 2013)
ABSTRAKÂ Lumbricus rubellus activity in agriculture area has give more positif character in within increase fertility soil on physics and land chemical. However for the moment agriculture lands trough thick and thin. As fertility land is down by dint offten use of essence chemistry like organofosfat pesticide clasification with profenofos active material by farmer in ficid. This research in then on to know influence profenofos insecticide toward fekundity and viability egg of Lumbricus rubellus at May until 2013 of July and Located in Biology Laboratory Kopertis Wilayah X. This research use randomised completely disign with 5 teratment and 5 recur. That treatment is profenofos insecticide with 0 %, 1 %, 0,2 %, 0,3 % and 0,4 % concentration and by syringe volume dose insecticide solution where commonly use is 1 ml for each treatment. Profenofos insecticide concentration where limit tolerance use for application at site is 0,1 %.PENGARUH INSEKTISIDA PROFENOFOS TERHADAP FEKUNDITAS DAN DAYA TETAS TELUR CACING TANAH(Lumbricus rubellus)